Features of the budget process under the conditions of marital state (Economics and region, 2022)
The full-scale invasion, which began on February 24, 2022, brought drastic changes to the budget process at both the state and local budget levels. Implementation of local budgets and provision of the budget process both at the level of administration and at the level of information and technological support was conditioned by the state of war and became subject to significant risks. A high level of budget process automation became a key matter of its implementation in 2022. The implementation of the information and analytical system (IAS) «LOGICA» made it possible to change and improve the level of automation of budget processes at the local level. IAS «LOGIKA» created a specification of rules for the implementation and support of all interrelated events (calendar events, changes in budget classifiers, changes in the forms of budget documents, etc.). In particular, «Local Budget» software provides complete automation of end-user processes that ensure the fulfillment of all budget obligations and carries out timely budget planning and approval for the future period of 2023. The article examines the main changes that took place in implementing local budgets under martial law. The main regulatory documents that were adopted to avoid the risks of non-implementation of the budget process by local financial bodies are defined. The possibility of financial provision by local budgets of special expenses during the war period was noted, including measures of territorial defense; assistance of the Armed Forces; evacuation/removal/relocation of the civilian population from the area where hostilities are taking place and dangerous areas to safe places (example); payment of transport services, fuel, and lubricants, provision of accommodation for citizens who left their homes due to hostilities, payment of other measures aimed at supporting the civilian population under martial law (example); carrying out an honorable burial ceremony of persons who died in the struggle for independence, sovereignty and territorial integrity of Ukraine. The conclusions state that the budget process at the local level during martial law ensured the needs of each individual territorial community and protected the interests of every citizen of Ukraine.
Keywords: Ministry of Finance of Ukraine; local budget; local financial bodies; head of military administration